{The geology and mineralogy of the Stypsi porphyry Cu-Mo-Au-Re prospect, Lesvos Island, Aegean Sea, Greece} - Voudouris, Panagiotis; Mavrogonatos, Constantinos; Melfos, Vasilios; Spry, Paul G.; Andreas Magganas; Alfieris, Dimitrios; Soukis, Konstantinos; Tarantola, Alexandre; Periferakis, Argyrios; Kołodziejczyk, Joanna; Scheffer, Christophe; Repstock, Alexander; et al. (Ore Geology Reviews, 2019)
The Stypsi Cu-Mo-Au-Re prospect, Lesvos island, is a shallow porphyry-epithermal system hosted within a middle Miocene microgranite porphyry, which was emplaced along NNE-, NW- and NE-trending structures, within trachyandesites to trachydacites and felsic pyroclastics of the Stypsi caldera. The mineralization comprises three stages: Stage I is characterized by magnetite-actinolite ± quartz in transitional and banded quartz veins mostly developed within the microgranite and the surrounding lavas related to calcic-potassic and propylitic alteration of the host rocks. In the banded veins, quartz is botryoidal, suggesting crystallization from a gel. Abundant vapor-rich inclusions in the bands produce a dark grey to black color. Within the veins, magnetite, chalcopyrite, bornite and native gold were followed in time by pyrite, hematite, sphalerite and galena. Stage I mineralization was synchronous and also postdates quartz formation in the veins, since it crosscuts and/or fills vugs in the center of the veins. Sulfides are associated with various combinations of K-feldspar, actinolite, epidote, chlorite, and calcite gangue minerals. Pyrite-molybdenite-chalcopyrite (Stage II) and late intermediate sulfidation epithermal veins (Stage III) overprint earlier mineralization and alteration, and are associated with sericite-calcite and sericite-kaolinite alteration of the porphyry system and spatially associated lavas, respectively. Molybdenite is widespread in the first two mineralization stages, with Re content ranging from about 0.3 wt% in Stage I to 1.96 wt% in Stage II. A barren silicic and advanced argillic (alunite-kaolinite) lithocap, is exposed on top of the porphyry-style mineralization and is crosscut by non-mineralized high-sulfidation epithermal chalcedony-barite veins. Bulk ore analyses of surface samples from the Stypsi prospect yielded values of up to 276 ppm Mo, 978 ppm Cu, up to 0.5 g/t Au, up to 3 g/t Ag, and up to 70 ppb Pd and Re. Fluid inclusion data indicate that the Stage I transitional and banded quartz veins were deposited at 420 °C–530 °C and at pressures up to 450 bars, from boiling hydrothermal fluids. The fluid in the veins consists of a brine (40–61 wt% NaCl equiv) that coexists with a lower salinity (6–14 wt% NaCl equiv) liquid phase and a low-density vapor-rich fluid. Fluid inclusions in quartz of the Stage III intermediate-sulfidation epithermal veins are characterized by relatively low homogenization temperatures (231 °C–288 °C) and salinities (up to 1.9 wt% NaCl equiv), which was the result of subsequent dilution of the moderately saline fluids by circulating meteoric water. This study verifies earlier works suggesting that Au-enriched felsic magmas are able to crystallize Re-rich molybdenite, and that Re may also be redistributed and enriched in later stages during the deposition of porphyry-style mineralization. The Stypsi prospect ressembles in many respects (e.g., Au grades, Cu/Mo ratios, the Re content of molybdenite and the presence of ore-grade calcic-potassic alteration), other porphyry Cu-Mo-Re-Au systems hosted in calc-alkaline rocks in northeastern Aegean, Greece.
Keywords: Banded quartz veins; Gold; Greece; Lesvos; Porphyry-epithermal; Re-rich molybdenite